(untitled) - Globerman, Steven (Englewood Cliffs, N.J., 1986)
This book provides a comprehensive coverage of all the basic concepts of financial management, including: time value of money, profit maximization vs. wealth maximization, financial statement analysis, dividend policies and more. It has been organized to suit the needs of students studying for degree courses, those in business and in practice as well as managers who are interested in the subject of financial management.
Keywords: International business enterprises,International economic relations; Management